(untitled) (Participação, 2011)
Com o propósito de contribuir, diante do desafio da extensão universitária da Universidade de Brasília-UnB e das práticas de educação popular, propomos algumas reflexões norteadoras Ã luz da educação libertadora de Paulo Freire, abordando a extensão como parte integrante da pesquisa e do ensino, o compromisso com a gestão democrática por uma nova sociedade socialista radicalmente humana, a transdisciplinaridade, a pesquisa-ação e a base territorial e virtual. Abstract: With the intention to contribute, ahead of the challenge of the university extension of the University of BrasiliaUnB and popular education practice, we propose some directing reflections to the light of the liberating education of Paulo Freire, approaching the extension as integrant part of the research and education, the commitment with democratic management for a new radically human socialist society, the multidisciplinarity, the research-action and virtual and territorial base.